Complete mitochondrial genome sequencing of central Indian domestic pig. Issue 1 (1st January 2016) - Singh, Ajit Pratap; Jadav, Kajal Kumar; Kumar, Dharmendra; Rajput, Nidhi; Srivastav, Awadh Bihari; Sarkhel, Bikash Chandra
Abstract: Domestic pig ( Sus scrofa domesticus ) is one of the important farm animal contributing 7% of the country's total animal protein sources in India. In the present study, random hexamer primer was used to amplify the complete mitochondrial genome of Central Indian domestic pig and resolved the complete mitochondrial sequence by shotgun sequencing followed by de novo assembly in MIRA version 4.0.5. The sequence assembly revealed to be 15, 827 bp mitogenome of pig (accession no. KT965278). The mitogenome in the present study has 99% homology with previously reported mitogenome of pigs from different parts of the world. The present study is the first report of complete sequence of mitogenome of pig from Indian subcontinent. Mitogenome analysis by MITOS web server revealed similarity of gene order, organization with the other pig breeds and vertebrates, comprising of 13 protein-coding genes, 22 tRNAs, 2 rRNAs and a control region. It was concluded that modified random hexamer can be successfully used for whole mitogenome sequencing using NGS without designing mitogenome-specific primer, thereby reducing cost and labor.